REORGANIZING THE MECHANISM OF SETTLING LABOR RELATIONS DISPUTES - Agusmidah Agusmidah; Mohammad Eka Putra; Affila Affila (Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractLaw No. 2 of 2004 was enacted to organize the mechanism of the settlement by involving the government (executive) through mediation and litigation. However, a number of complaints may have indicated some weakness in that mechanism. The objective was to identify the substance of Law No. 2 of 2004, which needs to be improved by formulating the ideal model. The data is consisted of primary and secondary data, which are gathered by using questionnaires to the industrial community in Medan and Deli Serdang Regency. The result showed that quick, accurate, fair, and inexpensive principles have not been implemented yet. Therefore, it is necessary to reorganize the mechanism of settling labor relations disputes. IntisariUndang-Undang Nomor 2 Tahun 2004 tentang Penyelesaian Perselisishan Hubungan Industrial ditetapkan untuk mengatur mekanisme penyelesaian yang melibatkan pemerintah (exekutif) melalui mediasi dan litigasi. Namun, sejumlah keluhan dapat menunjukkan kelemahan dalam mekanisme tersebut. Tujuannya adalah untuk mengetahui isi dari Undang-Undang Nomor 2 Tahun 2004 tentang Penyelesaian Perselisishan Hubungan Industrial, yang butuh untuk dikembangkan dengan merancang model ideal. Data terdiri dari data primer dan sekunder, yang dikumpulkan menggunakan kuisioner untuk komunitas industri di Medan dan Kabupaten Deli Serdang. Hasil menunjukkan bahwa prinsip cepat, akurat, adil, dan murah belum diimplementasikan. Maka, sangat diperlukan untuk mengatur ulang mekanisme penyelesaian sengketa hubungan kerja.